2012 41st International Conference on Parallel Processing Workshops 2012
DOI: 10.1109/icppw.2012.53
|View full text |Cite
|
Sign up to set email alerts
|

Hardware-Based Task Dependency Resolution for the StarSs Programming Model

Abstract: T am e r D a l l o u , B e n J u u r l i n k H a r dw a r e -b a s e d t a s k d e p e n d e n c y r e s o l u t i o n f o r t h e S t a r S s p r o g r amm i n g m o d e l C on f e r en c e ob j e c t , P o s tp r in t v e r s i on T h i s v e r s i o n i s a v a i l a b l e a t h t t p : / / d x . d o i . o r g / 1 0 . 1 4 2 7 9 / d e p o s i t o n c e -5 7 8 1 .Sugg e s t ed C i t a t i on D a l l o u , T am e r ; J u u r l i n k , B e n : H a r dw a r e -b a s e d t a s k d e p e n d e n c y r e s o l u t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In [9], it was shown that in order to reduce lookup time when a hash collision occurs, the hash table is replicated in a setassociative structure. This way, an input/output lookup requires only one visit to the Dependence Table, rather than multiples of that when implementing a linked-list structure inside a larger hash table, as was the case in [8].…”
Section: A Functional Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In [9], it was shown that in order to reduce lookup time when a hash collision occurs, the hash table is replicated in a setassociative structure. This way, an input/output lookup requires only one visit to the Dependence Table, rather than multiples of that when implementing a linked-list structure inside a larger hash table, as was the case in [8].…”
Section: A Functional Overviewmentioning
confidence: 99%
“…The list of configurable parameters and their experimental values are shown in Table I. The sizes of the different tables and lists in the Task Maestro were empirically determined, enlightened by previous work ( [8], Fig. 3.…”
Section: B Design Space Explorationmentioning
confidence: 99%
See 3 more Smart Citations